Basal Infusion versus Automated Boluses and a Delayed Start Timer for "Continuous" Sciatic Nerve Blocks after Ambulatory Foot and Ankle Surgery: A Randomized Clinical Trial. (10th May 2022) - Finneran, John J.; Said, Engy T.; Curran, Brian P.; Swisher, Matthew W.; Black, Jessica R.; Gabriel, Rodney A.; Sztain, Jacklynn F.; Abramson, Wendy B.; Alexander, Brenton; Donohue, Michael C.; Schaar, Adam; Ilfeld, Brian M.
Abstract : Background: The common technique using a basal infusion for an ambulatory continuous peripheral nerve blocks frequently results in exhaustion of the local anesthetic reservoir before resolution of surgical pain. This study was designed to improve and prolong analgesia by delaying initiation using an integrated timer and delivering a lower hourly volume of local anesthetic as automated boluses. The hypothesis was that compared with a traditional continuous infusion, ropivacaine administered with automated boluses at a lower dose and 5-h delay would (1) provide at least noninferior analgesia (difference in average pain no greater than 1.7 points) while both techniques were functioning (average pain score day after surgery) and (2) result in a longer duration (dual primary outcomes). Methods: Participants (n = 70) undergoing foot or ankle surgery with a popliteal–sciatic catheter received an injection of ropivacaine 0.5% with epinephrine (20 ml) and then were randomized to receive ropivacaine (0.2%) either as continuous infusion (6 ml/h) initiated before discharge or as automated boluses (8 ml every 2 h) initiated 5 h after discharge using a timer. Both groups could self-deliver supplemental boluses (4 ml, lockout 30 min); participants and outcome assessors were blinded to randomization. All randomized participants were included in the data analysis. Results: The day after surgery, participants with automated boluses had a median [interquartile range] pain score of 0.0 [0.0 to 3.0] versus 3.0 [1.8 to 4.8] for the continuous infusion group, with an odds ratio of 3.1 (95% CI, 1.23 to 7.84; P = 0.033) adjusting for body mass index. Reservoir exhaustion in the automated boluses group occurred after a median [interquartile range] of 119 h [109 to 125] versus 74 h [57 to 80] for the continuous infusion group (difference of 47 h; 95% CI, 38 to 55; P < 0.001 adjusting for body mass index). Conclusions: For popliteal–sciatic catheters, replacing a continuous infusion initiated before discharge with automated boluses and a start-delay timer resulted in better analgesia and longer infusion duration. Abstract : Patients undergoing foot or ankle surgery received popliteal–sciatic catheter-reservoir systems delivering ropivacaine by continuous infusion or by a bolus of anesthetic every 2 h. Those patients receiving bolus anesthetic experienced better pain control and effects of longer duration than those receiving continuous infusions.